Pemeriksaan Dan Pelatihan Deteksi Dini Kelainan Maloklusi Pada Anak Usia 6-8 Tahun Di Sekolah Dasar Muhammadiyah 1 Sidoarjo - Muntadir, Lila; Rinata, Evi; Setyawardana, Eka; Puspitasari, Dini Ayu; Tsabita, Nabila Fatya (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
The increasing incidence of malocclusion in children, often caused by unnoticed bad habits like thumb sucking and mouth breathing, highlights the need for prevention. This community service activity aimed to provide Dental Health Education (DHE) at Muhammadiyah 1 Elementary School in Sidoarjo to 41 children aged 6–8 years (21 boys, 20 girls), along with their parents and teachers, emphasizing the importance of maintaining dental health and preventing malocclusion caused by harmful habits.The methods used in this community service activity include enhancing Dental Health Education (DHE) through counseling to eliminate bad oral habits and prevent malocclusion. Efforts involve empowering junior dental health cadres to conduct oral health checks at schools, increasing students' knowledge about the impact of bad oral habits, educating on prevention and cessation of these habits, and implementing strategies to prevent malocclusion. Evaluation was conducted through dental molds, facial profile photographs, and intraoral photographs. The expected outcomes of this activity include increased public awareness of bad habits and their impact on dental health, as well as the establishment of dental health cadres at schools to perform regular dental health checks. Additionally, this activity will result in the publication of scientific articles and educational videos to be disseminated via electronic media. This community service successfully enhanced public knowledge about the importance of avoiding bad habits to prevent malocclusion, while also providing a sustainable platform for dental health education through collaboration among the community, schools, and faculties in the future.